Análisis del efecto antimicrobiano de doce plantas medicinales de uso ancestral en el Ecuador. - Azuero, Andrea (2014)
The antimicrobial activity of medicinal plants is a great benefit that can be obtain in order to have an effect either antibacterial or anti-fungal, and thus achieve heal any pathology that is present with one of these plants. In the trial of the antibacterial activity, medium Müller - Hinton and the strains of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus were used to culture by bringing two wells through which formed their respective halo of inhibition, a well was used to place the medication that was used to combat bacteria, in this case ciprofloxacin, and the methanolic extract of the plant was placed in the other well. In the antifungal activity assay, medium of potato dextrose agar was used for cultivation and the strain of Candida albicans, two wells were used and in a well was placed the medication, in this case ketoconazole, to control the growth of fungi, on the other well was placed the methanolic extract.